Experimental Philosophy and Cognitive Science in the Context of Comprehending Hybrid Intelligence: Philosophical and Anthropological Aspect - German E. Bokov; Helen V. Chapny (RUDN Journal of Philosophy)
The research considers experimental philosophy as a new philosophical movement. It emerged in Western intellectual thought in the 21st century against the background of the methodological crisis of analytic philosophy. Its representatives justify that the philosopher himself should actively master experimental methods of psychology and social sciences. They are opposing themselves to the so-called “cabinet” speculative philosophy. The main topic of their research is the “philosophical intuition” of ordinary consciousness. They also focus on the project of metaphilosophy. This movement has quite a few critics. They fear that if philosophy integrates with science it will lose its autonomy. Today one of the most promising interdisciplinary scientific fields is cognitive science, which actively uses experimental data. The research exploring the possibilities of dialogue between philosophy and cognitive science on a variety of issues, primarily on the question of consciousness and human cognitive activity. The research proves that by experimental philosophy we can mean a philosophy that is open to making sense of new data obtained experimentally. It retains its autonomy not being fully integrated into science but actively participates in scientific development, as well as acts as an ethical regulator of scientific and technological progress. We propose the interdisciplinary study of hybrid intelligence as one of the promising directions for the development of experimental philosophy. We reveal the main features of creating hybrid intelligent systems at the present stage. On the example of group collaboration of professionals of natural science and socio-humanities profile of the laboratory “Neurointerfaces” operating on the basis of the Research Center of neurotechnology of the Southern Federal University we demonstrate the feasibility of conducting research in experimental philosophy to study hybrid intelligence. The study emphasizes the importance and significance of bioethics and ethical regulation in the modern scientific and experimental field.